IMPACT OF DRYING METHODS AND SOLVENT EXTRACTION ON THE ANTIBACTERIAL PROPERTIES OF POMEGRANATE (PUNICA GRANATUM L.) - ., ADITYA (Food and Feed Research, 2026)
The current study aims to study the effects of three drying methods (freeze, tray, sun) and five solvents (methanol, ethanol, water, acetone, hexane) on the antibacterial properties of the by-product (peel) of pomegranate fruits against four bacterial strains (Pseudomonas aeruginosa, Escherichia coli, Bifidobacterium bifidum and Enterococcus faecalis). The results demonstrated that these extracts had a substantial antibacterial impact against the tested bacterial species. All pomegranate peel extraction fractions, containing methanol, ethanol, water and acetone, inhibited the growth of several Gram-positive and Gram-negative bacteria. The combination of freeze-drying process and methanol as extractive solvent demonstrated significantly higher antimicrobial activity (p